Technical Analysis of Sharia Stock Prices Using Moving Average and Relative Strength Index: Evidence from the Jakarta Islamic Index - Rahmat Ramadhan; Efi Sarifudin; Dede Sudirja (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of technical indicators on Sharia stock price movements in the Jakarta Islamic Index (JII). The research employs a quantitative approach using secondary data derived from historical stock prices of companies listed in the Jakarta Islamic Index. The sample consists of 10 Sharia-compliant companies, selected through purposive sampling, with a total of 141 observations during the period January 2024 to May 2025. The independent variables used in this study are the 20-day Moving Average (MA20) and the 14-day Relative Strength Index (RSI14), while stock price is used as the dependent variable. Multiple linear regression analysis is applied to examine the influence of the technical indicators on stock price movements. The results show that the Moving Average variable has a positive and significant effect on stock prices, with a regression coefficient of 1.007, a t-value of 215.090, and a significance level of 0.000. In contrast, the Relative Strength Index does not significantly influence stock prices, as indicated by a t-value of 0.486 and a significance level of 0.633. The simultaneous test indicates that the model is statistically significant with an F-value of 291.623. The coefficient of determination (R² = 0.999) shows that the independent variables explain 99.9% of the variation in Sharia stock prices. These findings suggest that the Moving Average indicator can serve as an effective technical analysis tool for predicting Sharia stock price trends in the Indonesian Islamic capital market.